2015
DOI: 10.1007/s00404-015-3764-4
|View full text |Cite
|
Sign up to set email alerts
|

Pycnogenol prevents peritoneal adhesions

Abstract: Pycnogenol was found to be effective at preventing surgery-related adhesions in an animal model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Bleeding, cauterization, ischemia, infections, and conditions that may damage the peritoneum may trigger adhesions [5][6][7] . While numerous cells such as mesothelial cells, histiocytes, fibroblasts, and lymphocytes help in healing the injured area, they also play a role in the development of peritoneal adhesion [2][3][4][5] . It has been demonstrated that adhesions are often the result of improper healing due to injured peritoneal tissues associated with oxidative stress 2 .…”
Section: ■ Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Bleeding, cauterization, ischemia, infections, and conditions that may damage the peritoneum may trigger adhesions [5][6][7] . While numerous cells such as mesothelial cells, histiocytes, fibroblasts, and lymphocytes help in healing the injured area, they also play a role in the development of peritoneal adhesion [2][3][4][5] . It has been demonstrated that adhesions are often the result of improper healing due to injured peritoneal tissues associated with oxidative stress 2 .…”
Section: ■ Discussionmentioning
confidence: 99%
“…In our study, in addition to parameters such as fibrosis and inflammation, we performed GSTP-1, Glut Red, SOD-1, and CAT staining to immunohistochemically examine oxidative stress parameters in tissues. After postoperative days 5 and 7, these adhesive strips progressed to persistent fibrous adhesions 2,13 . It was also reported that hypoxia directly promotes the production of free oxygen radicals in tissues 2,14 .…”
Section: ■ Discussionmentioning
confidence: 99%
See 3 more Smart Citations